Prasugrel switching from clopidogrel after percutaneous coronary intervention for acute coronary syndrome in Taiwanese patients: an analysis of safety and efficacy - Liu, Ping-Yen; Su, Cheng-Huang; Kuo, Feng-Yu; Lee, Wen-Lieng; Wang, Yi-Chih; Lin, Wei-Shiang; Chu, Pao-Hsien; Lu, Tse-Min; Lo, Ping-Han; Lee, Cheng-Han; Lan, Wei-Ren; Huang, Chien-Lung; et al. (Cardiovascular intervention and therapeutics, 2022)
The recommended maintenance dose of prasugrel for East Asian populations (i.e., Japanese and Taiwanese) is 3.75 mg as part of dual antiplatelet therapy (DAPT) for the prevention of recurrent ischemia and stent thrombosis in acute coronary syndrome (ACS). This modified dosage regimen has been established in studies conducted in Japan; however, the efficacy and safety of switching from clopidogrel to prasugrel DAPT among Taiwanese patients remain to be explored. In this phase IV, multicenter, single-arm, open-label study, we evaluated the 4-week pharmacodynamic response, and the 48-week safety outcomes of prasugrel 3.75 mg after a switch from clopidogrel in Taiwanese ACS patients. A total of 203 prasugrel-naïve ACS patients (over 90% male) who had received post-PCI clopidogrel DAPT for at least 2 weeks were enrolled from ten medical centers in Taiwan and subsequently switched to prasugrel 3.75 mg DAPT. Four weeks after the switch, P2Y12 reaction unit (PRU) values were significantly decreased in the total cohort (mean − 18.2 ± 48.1; 95% confidence interval − 24.9 to − 11.5, p < 0.001), and there was an overall consistent antiplatelet response in the treated subjects. The proportion of patients with high on-treatment platelet reactivity (HPR; PRU > 208) dropped from 23.5 to 10% ( p < 0.001). Female sex was associated with a greater PRU reduction with prasugrel, whereas HPR at baseline, age ≥ 65 years, and body mass index ≥ 25 best predicted HPR at Week 4. Throughout the 48-week treatment with prasugrel, the incidences of MACE (1.0%) and TIMI major bleeding (2.0%) were rather low, accompanying an acceptable safety profile of TIMI minor (6.4%) and non-major, non-minor clinically relevant bleeding (3.0%). Overall, switching to the maintenance dose of prasugrel (3.75 mg) was observed to be effective and well tolerated among post-PCI ACS patients in Taiwan. Clinical Trial Registration Number: NCT03672097.